Digital controller for stepping motor-driven X-ray diffractometer - Naval, Prospero C. Jr (Philippine Engineering Journal)
Presented is a stepping motor controller for the Philips PW 1050 Vertical Goniometer featuring crystal-controlled scan rates of 4, 2, 1, 1/2, 1/4 and 1/8 degrees per minute in the continuous scan mode and step sizes of 0.005, 0.01, 0.02, 0.025, 0.05, 0.1, 0.2 and 0.5 degrees when operated in the step scan mode. A slew rate of 96 degrees per minute is provided for positioning purposes. The TTL implemented design accommodates upgrading to higher levels of automation by a simple substitution of the control logic section.